2019
DOI: 10.1016/j.jsha.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of cardiac surgery in adults with congenital heart disease: A single center experience

Abstract: ObjectivesAdult survivors with congenital heart diseases represent a large and growing population, yet the published data does not represent the magnitude of their needs specifically in the Middle East. We aimed to review our experience at King Faisal Heart Center, Riyadh, Saudi Arabia for the outcome of adult patients with congenital heart disease who underwent either primary or redo surgery.MethodsA retrospective study at a tertiary care hospital. All patients who underwent surgery either as the first surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Our results compare favorably with the published literature where mortality ranges from 0.7% to 9.4%. 2 , 3 , 4 , 5 Our contemporary cohort also compares well to reported morbidity rates with a recent similar single-center study reporting rates of AKI of 2.1%, stroke of 1.4%, and prolonged ventilation of 11.4%. 2 Our rate of prolonged ventilation greater than 7 days was 3.9% in the “after” group.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results compare favorably with the published literature where mortality ranges from 0.7% to 9.4%. 2 , 3 , 4 , 5 Our contemporary cohort also compares well to reported morbidity rates with a recent similar single-center study reporting rates of AKI of 2.1%, stroke of 1.4%, and prolonged ventilation of 11.4%. 2 Our rate of prolonged ventilation greater than 7 days was 3.9% in the “after” group.…”
Section: Discussionsupporting
confidence: 82%
“… 2 Mortality after cardiac surgery in patients with adult congenital heart disease (ACHD) ranges from 0.7% to 9.4%. 2 , 3 , 4 , 5 , 6 …”
mentioning
confidence: 99%
“…The incidence of mortality was 13.455 times higher in patients with a cut-off value of ≥0.7 in their ACHS mortality scores. Abouelella et al [17] reported a postoperative complication rate of 18%, similar to the rate of 28% stated by Mascio et al [18] The reported incidence of neurological complications is 7%. [19] In our study, postoperative complications were detected in 13.7% of the cases (n=28), and it is consistent with the literature (Table 4).…”
Section: Discussionsupporting
confidence: 71%
“…In this study, they divided the patients into 152 groups and determined an ACHS mortality score ranging from 0.1 to 3.0 for each. In 2019, Abouelella et al [17] stated that the ACHS score is currently the best predictor of mortality in GUCH patients and that the mortality rate was 4%.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of our present cohort of CHD patients with severe postoperative hyperbilirubinemia showed an overall incidence of postoperative AKI of 59.3% and an in-hospital mortality rate of 10.5%. The reported AKI incidences in CHD patients who underwent CPB cardiac surgery in previous studies ranged from 11 to 51% [ 9 , 10 , 11 , 12 , 13 ], and the in-hospital mortalities ranged from 1.1 to 4% [ 10 , 14 ]. The discrepancies were most likely attributed to the differences in disease severity of the included patients between the studies.…”
Section: Discussionmentioning
confidence: 99%